Pelatihan Proses Pembuatan Kerajinan Gantungan Kunci Dari Kawat Bulu Pada Siswa Kelas IV Mis Hidayatul Muhajirin - Puput Melati Sukma; Ratna Kartika Sari; Istiyati Mahmudah (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
The training activity of making key chains from feather wire was carried out at MIS Hidayatul Muhajirin as a form of contribution in improving fine motor skills and creativity of fourth grade students. Based on the initial observation, it is known that students have not been much involved in creative activities based on hand skills, so efforts are needed to provide appropriate stimulation. The main problem identified was the limited opportunities for students to develop creativity and skills through fun hands-on activities. This training was carried out through several stages, namely identification of needs, activity planning, counseling on tools and materials, exposure to keychain making, and practical sessions accompanied by facilitators. The results of the activity showed that the students participated in the training with enthusiasm and were able to produce diverse and creative works. Analysis of the results showed an increase in students' skills in technical and attitudinal aspects, such as independence, accuracy, cooperation, and self-confidence. The implementation of this activity also provides space for students to express ideas freely and fun. With documentation of the work as a form of evaluation, this training is expected to be a model of educational activities that are applicable and able to enrich the learning process at the SD / MI level. In addition, this activity encourages students' active involvement in the learning process that not only focuses on cognitive aspects, but also affective and psychomotor aspects. Thus, this training makes a significant contribution to students' character building and creates an inclusive, creative and fun learning environment for all learners.